Measurement of Iron Content and Detection of Sulfate Ion in Traditional/Industrial Canned Black Olives in Iran - Asadi-Sharifi, Tayebeh; Peivasteh-Roudsari, Leila; Molaee-Aghaee, Ebrahim; Nazmara, Shahrokh; Sadighara, Parisa; Khaneghah, Amin M. (Current Nutrition & Food Science, 2020)
Background: Black olive contains considerable concentrations of phenolic compounds, which can result in a higher antioxidant component compared with green olives. Sometimes, as food fraud, the use of unwanted substances has been observed such as iron sulfate or iron particles for blackening olives, eventually causing adverse effects on the tissues of the digestive tract, brain, kidney, and liver in the consumer. The main purpose of this study was to determine flavonoids, iron content and ion sulfate in canned black olives. Methods: Canned black olive from inland/imported and traditional/industrial samples were collected. The amount of iron, sulfate ion, and flavonoids content were measured by ICP-OES and spectrophotometer, respectively. Results: Industrial black olives (brand N) from Turkey showed the highest iron content (110.17 mg/kg) and traditional black olives purchased from Rudbar, showed the lowest iron content (6.72 mg/kg). These values were lower than the iron limit in canned black olives (150 mg/kg). The highest and lowest levels of sulfate were also found in the traditional black olive of Rudbar and industrial black olives of Greece, respectively. Sulfate amount was determined between 23.225-82.102 mg/kg. Traditional black olives of Roudbar had the highest flavonoid, and the lowest flavonoid content was shown by the industrial black olive of Turkey. The pH was in the range of 4.4-4.8, indicating that the pH of any of the samples was not higher than the standard maximum level. Conclusion: According to the results of this study, iron sulfate has not been added intentionally to the collected samples.
Keywords: iron